PENGARUH BUDAYA ORGANISASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI DI TVRI GORONTALO - Nurain Ikhsan; Yosef P koton; Harson Towalu (Journal of Economic, Business, and Administration (JEBA), 2023)
The purpose of this research is to find out and analyze the influence of organizational culture and discipline on employee performance at TVRI Gorontalo. study uses a quantitative method, with a census sample of 87 employees of TVRI Gorontalo. Data analysis using multiple regression. The results showed that organizational culture partially had no significant effect on the performance of TVRI Gorontalo employees, Discipline partially had an insignificant effect on the performance of TVRI Gorontalo employees, organizational culture and discipline simultaneously had a positive and significant effect on employee performance at TVRI Gorontalo